PERAN PEMIMPIN INFORMAL PADA PRAKTIK TRADISI KORE-METAN DI DESA AITEAS, MUNICIPIO MANATUTO, TIMOR LESTE - Soares, Evaristo; Prabawa, Titi Susilowati; Sasongko, Gatot (Universitas Kristen Satya Wacana, 2020)
Strengthening the role of village communities must be carried out in order to build reform for the village itself. One of the most prominent social empathy attitudes as a symptom of rural community life is mutual cooperation. In the Kore-Metan traditional practice, the people of Aiteas Village, Municipio Manatuto, Timor Leste also apply the principle of mutual cooperation. In the effort to develop tradition, the most competent is the customary leader, because he is the informal leader of the tribe. This study aims to determine the role of informal leaders in the practice of Kore-Metan tradition in Aiteas Village. This research use desciptive qualitative approach. Data obtained by interview. The research was conducted in Aiteas Village, Posto Administrative Manatuto, Municipio Manatuto, Timor Leste. Based on the research results, the practice of the Kore-Metan tradition has a function for the people of Aiteas Village: First, the Kore-Metan tradition is a tradition passed down from generation to generation as a useful historical heritage. Second, it gives legitimacy to the beliefs, institutions and rules that already exist in Aiteas Village. Third, the Kore-Metan tradition provides a convincing symbol of collective identity, in this case loyalty to traditional ties and local cultural values. Fourth, the Kore-Metan tradition as a means of consolation. The role of the traditional leader of Aiteas Village is very important in the practice of the Kore-Metan tradition. The role of the Traditional Leader of Desa Aiteas in the practice of the Kore-Metan tradition, namely first, to give direction to the socialization process; second, the inheritor of traditions, beliefs, values, norms and knowledge; third, to unite society; and fourth, turn on the control control system. Social institutions through the role of the Traditional Chairman of Aiteas Village in the practice of the Kore-Metan tradition can be a means for building the character of the Aiteas Village community, because these social institutions contain the values ​​of mutual cooperation, responsibility, adherence to customary values, as well as community unity and integrity.